2020
DOI: 10.1080/17408989.2020.1850667
|View full text |Cite
|
Sign up to set email alerts
|

Perceived teachers’ behavior and students’ engagement in physical education: the mediating role of basic psychological needs and self-determined motivation

Abstract: Background: Although several studies that rely on self-determination theory have shown the positive interrelations among perceived need supportive learning environment, needs satisfaction, quality of motivation, and desired outcomes in the context of physical education, only few studies have tested so far the full sequence of relations within a single integrated model. Purpose: The main aim of this study was to test whether indeed needs satisfaction and in turn quality of motivation mediate the relations of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 59 publications
11
97
1
5
Order By: Relevance
“…In this sense, the data analysis reported a positive correlation among autonomous motivation (intrinsic motivation and identified regulation), higher basic psychological needs satisfaction, higher personal and social responsibility development, and a better school climate perception. This correlation between motivation and basic psychological needs satisfaction was already verified by Leo et al [ 45 ] and Kaiser et al [ 46 ], who also found a positive correlation, as this study stated. As Leo et al [ 45 ] remarked, specifically in the educational context, in Physical Education lessons, the teaching methodology used by teachers, conditions whether this correlation exists or not.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this sense, the data analysis reported a positive correlation among autonomous motivation (intrinsic motivation and identified regulation), higher basic psychological needs satisfaction, higher personal and social responsibility development, and a better school climate perception. This correlation between motivation and basic psychological needs satisfaction was already verified by Leo et al [ 45 ] and Kaiser et al [ 46 ], who also found a positive correlation, as this study stated. As Leo et al [ 45 ] remarked, specifically in the educational context, in Physical Education lessons, the teaching methodology used by teachers, conditions whether this correlation exists or not.…”
Section: Discussionsupporting
confidence: 89%
“…This correlation between motivation and basic psychological needs satisfaction was already verified by Leo et al [ 45 ] and Kaiser et al [ 46 ], who also found a positive correlation, as this study stated. As Leo et al [ 45 ] remarked, specifically in the educational context, in Physical Education lessons, the teaching methodology used by teachers, conditions whether this correlation exists or not. In turn, the relation between personal and social responsibility and motivation (also from an SDT perspective), was studied by Manzano-Sánchez et al [ 26 ] and Manzano-Sánchez and Valero-Valenzuela [ 2 ].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it forms a broad framework that facilitates the understanding of intrinsic motivation, extrinsic motivation and psychological well-being, issues of direct importance for educational centres [ 8 ]. Following the SDT, Ryan and Deci [ 6 ] establish that people have three basic psychological needs that are essential and inherent (autonomy, competence and relatedness) which promote optimal functioning [ 9 ], but whose frustration can lead to maladjustment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent SDT-based research has highlighted that autonomy support is an essential part of a need-supportive style along with competence support (or structure) and relatedness support (e.g., Aelterman et al, 2019;Leo et al, 2020;Rocchi et al, 2017). Similarly, controlling (or autonomythwarting) behaviours represent a meaningful part of a need-thwarting (or demotivating) style together with competence-thwarting (or chaos) and relatedness-thwarting (cold environment) behaviours (e.g., Aelterman et al, 2019;Leo et al, 2020;Rocchi et al, 2017). Future research could do well when adopting a broader conceptualization of PE teachers' interpersonal behaviour as a theoretical framework.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%